Herpes simplex virus type 1-specific immunity induced by peptides corresponding to an antigenic site of glycoprotein B. - Mester, J C (1990)
Herpes simplex virus (HSV) envelope glycoproteins are the prime targets of adaptive antiviral immunity. Previous investigation identified a protective, neutralizing, glycoprotein B1 (gB-1)-reactive monoclonal antibody (MAb B6) and localized the linear epitope recognized by the MAb to residue 84 of gB-1. Three overlapping peptides (two 20-mers and one 18-mer), together spanning amino acids 63 to 110 of the wild-type sequence of gB-1, were synthesized and analyzed for their ability to stimulate immunity which cross-reacts with HSV-1. All stimulated some level of response. Two peptides, the gB 18-mer and 20.1-mer, were recognized by MAb B6 and HSV-immune antibody but were unable to stimulate virus-neutralizing antibody or serum able to protect against zosteriform spread in vivo. The 20.2-mer peptide, however, which was not recognized by MAb B6 or HSV-generated immune antibody, stimulated the production of neutralizing antibody and serum able to protect against zosteriform spread. Immunization with all of the peptides was able to enhance viral clearance of a low dose of HSV-1 in an ear challenge model and induce antibody reactive in antibody-dependent complement-mediated lysis of HSV-1-infected cells in vitro. These results are the first report of HSV immunity induced by peptides corresponding to gB and indicate that the best immunogen, in terms of stimulating neutralizing antiserum able to protect in vivo against HSV-1, was a peptide not recognized by HSV-immune mechanisms or by the MAb used to localize it.